(De)legitimation Strategies and Presidential Legitimacy in Trial Memoranda - Comparative Case Study of the 2020 Impeachment Trial of President Donald Trump - Veräjänkorva, Emmi (My University, 2023)
Presidential power and legitimacy provide an interesting topic of research in the tumultuous socio-political climate of the United States as the role of presidents have increased in recent years. One of the recent upheavals was the first impeachment trial of President Donald Trump in 2020. This thesis contributes to the discussion of presidential power and its state in the United States by analyzing the trial memoranda of the prosecution and the defense of the 2020 impeachment trial of President Trump. In the qualitative analysis of the thesis, a three-dimensional framework by Norman Fairclough is utilized. On the textual level of analysis, a theory of (de)legitimation strategies by Theo Van Leeuwen is applied. The theoretical backgrounds of presidential powers and impeachments, and the theoretical concept of legitimacy enable a comprehensive approach to analyze and discuss the impeachment trial of President Trump and how presidential power and legitimacy are created. The findings of the (de)legitimation strategies on the first level of analysis reveal that the House of Representatives uses strategies to legitimize their own actions and the impeachment trial, while they delegitimize the actions of the president. Respectively, the Office of White House Counsel legitimizes the actions of the president whilst they delegitimize the actions of the House and the entirety of the impeachment inquiry. The two other levels of analysis display how meanings are constructed through interpretations of presidential power, the Constitution, and legitimacy. Furthermore, the analysis demonstrates a polarization of the political field in the United States.
Keywords: critical discourse analysis, presidential power, legitimacy, presidential impeachment, the Constitution, United States